Dance Works : Stories of Creative Collaboration - Orr, Allison (Book collections on Project MUSE., 2023)
"Ride along with choreographer Allison Orr and her civic collaborators as they reflect on their dances together. In 2001, Allison Orr made a dance with 13 City of Austin firefighters. Over the next 20 years, her unique practice of collaborating with city employees flowered into civic storytelling through movement at public pools, tableaus of power line workers shimmying up 40' poles in front of 5000 people, and intricate choreography of trash trucks on a misty tarmac. Part memoir, part guide, the artist reflects on her major collaborations and shares interviews with people she's made dances with over the past two decades. Power line workers, sanitation workers, and firefighters reflect on their memories of performing with Forklift and the lasting impact those dances made. Alongside larger conversations in the arts, Orr offers a look at how to create community-based art projects, how the creative process can bring people together to address civic issues, and the beauty of choreographing the day to day. An appendix and online companion include budget information, full cast and crew lists, participant survey results, and more"--